PENGGUNAAN DAUN KANGKUNG SEBAGAI PENGGANTI RUMPUT LAUT DALAM PEMBUATAN NORI - Dewi Fitriani; Putri Irawati (JURNAL PARIWISATA VOKASI, 2021)
This study aims to determine the differences in taste, nutritional content, and production costs between nori made from kale leaves and seaweed nori which will produce the best organoleptic test results and are much preferred by panelists and also as a food diversification made from kangkong leaves. The collection method used is the experimental method. Data collection techniques were carried out through product experiments, distributing questionnaires, and observing. While the data analysis technique using a hedonic scale. Based on the results of the study, it can be seen that professional panelists stated that kangkung nori had better results than seaweed nori. This is based on several professional panelists' comments stating that seaweed nori has a slightly fishy aroma and the taste is easily lost when put in the mouth. Meanwhile, according to consumer panelists, seaweed nori is more delicious than kale leaf nori. This is based on consumer panelists' comments stating that the nori leaves of kale have a slightly wrinkled texture and a slightly browner color; nutritional content in terms of calories, kangkung nori is higher than seaweed nori. Meanwhile, in terms of protein, seaweed nori is higher than kale leaf nori. In terms of fat, kangkung leaf nori is lower than seaweed nori and in terms of carbohydrates, kangkung leaf nori is lower than seaweed nori. So, it can be concluded that the nutrition of nori leaf kangkung is better than seaweed nori.; and kangkung nori has a lower production cost compared to seaweed nori, which is Rp. 7.508. With a difference of Rp. 2,492. for each pack. Suggestions given for solving the problem are 1). The texture of the experimental nori is slightly more wrinkled, the author suggests that in the printing process it is left to dry completely after that in the oven; 2) It is better to choose kale that is still fresh and has bright leaves because it will affect the color results of the nori leaves so that the color is not pale/brown; and 3) Choose kale leaves that are still fresh, not old/hard and not wilted because such leaf quality will reduce the nutritional content.